Analisis Peranan Strategi Marketing Funding Dalam Peningkatan Jumlah Nasabah dan Dana Pihak Ketiga: - Muhammad Hamdan 'Ainulyaqin (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2021)
Indonesia was ranked first in the global Islamic financial market at the 2019 Sharia Economic and Financial Research Forum (FREKS), where the market share in the Islamic banking sector had reached 6.01% and the OJK is targeting in 2023 the Islamic banking market share of 15%, wrong one indicator of improvement is by increasing the number of accounts and the amount of Third Party Funds (TPF). The purpose of this study is to determine what strategies are used by the Marketing Funding of the BPRS Harta Insan Karimah Cikarang Branch to increase the number of customers or accounts and the amount of TPF. Then what is the role of the strategy used by Marketing Funding in increasing the number of customers and the number of deposits. The pick-up strategy implemented by BPRS Harta Insan Karimah Cikarang branch is an excellent service provided to each customer, this strategy is considered to provide convenience to customers in savings and deposit products because the transaction can be done at home and the Marketing Funding team will visit the customer's house. If the strategy is to pick-up properly, the target number of customers will be achieved and theoretically the amount of deposits will increase as well. This study uses a qualitative method with a descriptive approach, so that the researcher will explain or describe the results of the study in verbal or descriptive form so that it is easy to understand. The research method used in data collection includes interviews, observation, documentation and literature study. The results showed that the strategy used by marketing funding was the pick-up strategy, where deposits, withdrawals and account opening could be done at the customer's house with prior confirmation with the Marketing Funding team so that the interaction was built between the two. The role of this strategy was significant in increasing the number of customers in 2017 reaching 11.11% and in the following year the number of customers increased by 10.79%. However, the role of the pick-ball strategy is not significant in increasing TPF, in other words the increase in the number of customers does not mean that TPF will increase as well, seen in 2015 of 10.79%, and the next 2 years decreased consecutively, namely -21.77% and -9.53%, in 2018 the amount of TPF increased again by 14.65%. Other alternative strategies that can be implemented by BPRS Harta Insan Karimah Cikarang Branch are maximizing social media as a means of advertising, recruiting SDI Marketing Funding team, socializing to guardians of affiliated school students, giving souvenirs to customers who can refer BPRS HIK, sponsoring the community agenda or institutions, as well as Improving the schedule for collecting funds and improving the information system.